Accessing behavioral intention to buy medical Takaful insurance among muslim visitors in Hospital Kepala Batas, Pulau Pinang / Nur Iylia Fatin Mohamad Rasul - Mohamad Rasul, Nur Iylia Fatin (Faculty of Business and Management, 2018)
Nowadays, people are encouraged to take insurance to protect them from unexpected tragedies such as death, losses and damages from financial loss. Hence, in this study, the main objective is to measure the intention of the customers to buy an insurance focusing on the Medical Takaful product. Besides that, this study also aims to examine the effect of four selected cause factors (i.e. Attitude, Subjective Norm, Willingness to Pay, and Perceived Behavioral Control) toward Behavioral Intention to buy a Medical Takaful Insurance among the target population. The study was conducted at Hospital Kepala Batas, Pulau Pinang, where focusing on Muslim visitors and 210 respondents were participated in this study. By using the Multiple Linear Regression (i.e. MLR) analysis, the findings indicated that, all these four selected cause factors are positively significantly influenced the buying intention of Medical Takaful Insurance, where these four factors can explained around 50% of variance explained toward the dependent variable. Hence, it is indicated that, as for increasing the buying intention of Medical Takaful Insurance among this community, the Takaful Insurance Company should focus on these four selected causes' factors.